PENINGKATAN HASIL BELAJAR MELALUI MEDIA BAMES MENGURAIKAN DAN MENYUSUN BILANGAN DI SDN WONOKUSMO IV SURABAYA: penelitian tindakan kelas - Rachmawati, Rachmawati; Hendratno, Hendratno; Hutomo Putri, Paramananda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find out whether bames media is able to improve learning outcomes in learning to decipher and arrange numbers at SDN Wonokusumo IV Surabaya. This research method uses classroom action research. The research consists of pre-cycle, cycle I, cycle II. The cycle consists of planning, implementing, observing and reflecting. The subjects of this research were 26 grade 1 children at SDN Wonokusumo IV Surabaya. Data analysis techniques use data using quantitative and qualitative approaches which are analyzed descriptively. The results of this research in the pre-cycle were 57% with 21 who had not yet completed, followed by cycle 1 which was 66% with 11 students who were still incomplete, cycle 2 experienced an increase of 89% and 3 students who were still incomplete. Based on these results, it shows that Bames media can improve learning outcomes for deciphering and arranging numbers at SDN Wonokusumo IV.